1998
DOI: 10.1074/jbc.273.50.33548
|View full text |Cite
|
Sign up to set email alerts
|

Motif Mutation of Bradykinin B2 Receptor Second Intracellular Loop and Proximal C Terminus Is Critical for Signal Transduction, Internalization, and Resensitization

Abstract: In the search for the structural elements participating in signal transduction, internalization, and resensitization of the bradykinin B2 receptor, we identified two critical motifs, one in the second intracellular loop (IC2), the other in the proximal C terminus. We previously described the contribution of tyrosines within each of the two motifs (Tyr interact cooperatively in conjunction with at least two separate signaling functions. Given these results, a molecular model of the receptor was generated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 45 publications
4
83
1
1
Order By: Relevance
“…However, these regions have previously been implicated in numerous signaling pathways and processes. The importance of the second intracellular loop in G protein coupling has been experimentally confirmed for other GPCRs, including the bradykinin B 2 (62), ␣ 2A adrenergic (63), and type B endothelin receptors (64). Using molecular modeling, Prado et al (62) produced evidence that the distal i2 loop and proximal carboxyl terminus of the bradykinin B 2 receptor may interact with each other to mediate receptor internalization and resensitization, in addition to G protein coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these regions have previously been implicated in numerous signaling pathways and processes. The importance of the second intracellular loop in G protein coupling has been experimentally confirmed for other GPCRs, including the bradykinin B 2 (62), ␣ 2A adrenergic (63), and type B endothelin receptors (64). Using molecular modeling, Prado et al (62) produced evidence that the distal i2 loop and proximal carboxyl terminus of the bradykinin B 2 receptor may interact with each other to mediate receptor internalization and resensitization, in addition to G protein coupling.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the second intracellular loop in G protein coupling has been experimentally confirmed for other GPCRs, including the bradykinin B 2 (62), ␣ 2A adrenergic (63), and type B endothelin receptors (64). Using molecular modeling, Prado et al (62) produced evidence that the distal i2 loop and proximal carboxyl terminus of the bradykinin B 2 receptor may interact with each other to mediate receptor internalization and resensitization, in addition to G protein coupling. Berg et al (65) showed that the i2 loop of the 5-HT 2C receptor is important for G␣ q coupling, and that different isoforms of the receptor produced via RNA editing in regions of the second intracellular loop varied in their ability to induce second messengers.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular model of the human NK-1R was built using the topological arrangement of the transmembrane helices of rhodopsin (18 -20) following procedures detailed previously (21,22). The loops connecting the transmembrane helices were generated using a metric matrix distance geometry program, employing the distances between the transmembrane helices as restraints.…”
Section: Methodsmentioning
confidence: 99%
“…The model contains the structural features of the second extracellular loop (EC2) of the NK-1R as recently determined by high resolution NMR (13). The loop plays an important role in SP binding, as evidenced by previous photoaffinity studies (13)(14)(15)(16)(17) a covalent bond with a residue in the proximal N terminus of the NK-1R (residues [11][12][13][14][15][16][17][18][19][20][21]. The structural consequences of Bpa 3 SP interacting with two sites, either sequentially or simultaneously, are examined here by extensive molecular dynamics simulations.…”
mentioning
confidence: 99%
“…С другой стороны, эта мутация полностью восстанавливала сопряжение рецептора с G-белком, которое уничтожалось при замене остатка Tyr 131 (Tyr 129 в Б 2 Р человека) входящего в состав DRY-мотива (II внутриклеточная петля). Различные дополнительные мутации аминокислотных остатков привели к выводу, что аминокислотные остатки тирозина вовлечены во взаимодействие, которое контролируется остатком Tyr 137 (Tyr 135 в Б 2 Р человека), что является очень важным для активации сопряжения c G белком и последующей интернализации рецептора [77].…”
Section: 4unclassified